Novel variant in the leptin receptor (LEPR) gene and its association with fat quality, odour and flavour in sheep - A. Gunawan; F. W. Pramukti; K. Listyarini; M. A. Abuzahra; J. Jakaria; C. Sumantri; I. Inounu; M. J. Uddin (Journal of the Indonesian Tropical Animal Agriculture, 2019)
The aim of this study was to investigate the association and expression of LEPR with fat quality, flavour and odour in sheep. A total of 47 rams were used in this study. Fatty acids composition, BCFA (Branch Chanin Fatty Acids; MNA, MP, MOA, and EOA) and skatole (MI) representing fat quality, flavour and odour in sheep were measured at ages of 10-12 months old. Identification of novel variant and expression analysis of LEPR gene with different fat quality, odour and flavour were performed by PCR RFLP and qRT-PCR, respectively. A SNP in genomic region g.40854778 A>C of the LEPR gene was associated (P<0.05) with fat quality of saturated fatty acids (SFA) including [tricosanoic acid (C23:0) and tetracosanoic acid (C24:0)] and poly unsaturated fatty acid (PUFA) [docosahexaenoic acid (C22:6n3)]. However, the novel variant of LEPR was not significantly associated (P<0.05) with fat content, odour and flavour (MNA, MP, MOA, EOA, and MI). The mRNA expression analysis showed that LEPR mRNA expression was higher (P<0.01) in sheep found at the AA genotype. It could be concluded that variant SNP in the LEPR may contribute to fatty acid composition without influencing odour and flavour traits in sheep.